Brand dan Arsitektur Dalam Tuntutan Pasar Global - Onie Dian Sanitha; V.G. Sri Rejeki; A. Rudyanto Soesilo (Jurnal Lingkungan Karya Arsitektur (LingKAr), 2022)
Abstract : Architecture as a function container reminds us that image is never out of a use. A strong image is able to form a strong brand as a representation of use. When brand meets architecture, the challenge lies in the economic context, competition in presenting profits. The Principles of Economics challenge the originality of quality architectural designs. However, there is a tendency for similar visual concepts to emerge due to the power of well-known brands in the world of architecture with phenomenal characteristics. Through literature study, this paper will formulate theoretical ideas in responding to these challenges to find the formulation of the initial design basis that makes the design become original and have good quality. Keywords: brand, image, architecture, economic principles Abstrak : Arsitektur sebagai wadah fungsi menjadi pengingat bahwa citra tidak pernah lepas dari guna. Citra yang kuat mampu membentuk brand yang kokoh sebagai representasi guna. Ketika Brand bertemu dengan Arsitektur maka tantangannya terletak pada konteks ekonomi, yakni persaingan dalam menghadirkan keuntungan. Prinsip Ekonomi menantang desain perancangan arsitektur yang orisinil dan berkualitas. Namun muncul kecenderungan konsep visual yang hampir serupa akibat kekuatan brand ternama di kelas arsitektur dengan ciri khas yang fenomenal. Melalui studi kepustakaan, penulisan ini akan merumuskan gagasan-gagasan teoretis dalam menjawab tantangan tersebut sehingga menemukan rumusan landasan perancangan awal yang menjadikan desain dapat orisinil dan berkualitas. Kata Kunci : brand, citra, arsitektur, prinsip ekonomi